Pengaruh Perputaran Modal Kerja dan Pertumbuhan Penjualan Terhadap Profitabilitas dengan Likuiditas sebagai Variabel Moderating pada Perusahaan Subsektor Pertambangan Logam Mineral yang Terdaftar di Bursa Efek Indonesia - Ema Yuliani; Marlina Widiyanti; Andriana, Isni (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to examine how the effect of working capital turnover and sales growth on profitability with liquidity as a moderating variable listed on the Indonesia Stock Exchange in the 2018-2022 period. Using secondary data from 10 companies, the results show that working capital turnover has a positive effect on profitability and sales growth has a positive effect on profitability. Moderation Regression Analysis is also used to test the moderating effect of liquidity. Liquidity has a positive effect on profitability and is able to moderate and directly influence the relationship between working capital turnover and sales growth on profitability. The implication of this research is that investors must pay attention to information about liquidity and macroeconomic conditions.